IMPAIRED BALANCE OF CLOTTING FACTORS IN LIVER CIRRHOSIS - Volkanovska, Anche; Dejanova, Violeta; Isjanovska, Rozalinda; Nikolovska Trpchevska, Emilija; Nikolova, Dafina; Deriban, Gjorgji; Todorovska, Beti; Grivcheva Stardelova, Kalina; Labudovikj, Danica (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2023)
Liver cirrhosis (LC) has been accepted as prototype of a disease with acquired prohemorrhagic diathesis. However, as the synthesis of all coagulant factors is affected, a rebalanced but fragile hemostasis is maintained. With increasing disease severity, a disproportion between levels of certain coagulants occurs that can lead to prothrombotic tendency. We aimed to evaluate the levels of factor VIII (FVIII), protein C (PC) and their ratio (FVIII/PC) as the main determinants of thrombin generation in patients with LC at different stages of disease. Fifty patients with LC were divided in three groups according to LC severity using the Child-Turcotte-Pugh Score (CTP-A, CTP-B, CTP-C). The levels of FVIII and protein C were measured in sodium citrate plasma on Siemens, BCS XP Blood Coagulometer. The levels of FVIII, PC and FVIII/PC were compared between the groups and a correlation of their values to MELD score was performed. Plasma levels of FVIII increased with severity of the disease, with concurrent statistically significant decrease of plasma PC levels (p=0.0008). This was accompanied with statistically significant increase of the FVIII/PC ratio (p=0.0004) indicating hypercoagulable state in advanced stage of the disease. A significant correlation to MELD score was identified for PC in group CTP-B and CTP-C and for FVIII/PC ratio in group CTP-C. As liver cirrhosis severity increases, a disproportion in plasma levels of the most powerful determinants of thrombin generation occurs. This could be the explanation for the observed increased risk of venous thromboembolism in patients with liver cirrhosis.
Keywords: liver cirrhosis; hemostasis; prothrombotic state